2019
DOI: 10.7150/thno.35914
|View full text |Cite
|
Sign up to set email alerts
|

COL4A2 in the tissue-specific extracellular matrix plays important role on osteogenic differentiation of periodontal ligament stem cells

Abstract: Periodontal ligament stem cells (PDLSCs) can repair alveolar bone defects in periodontitis in a microenvironment context-dependent manner. This study aimed to determine whether different extracellular matrices (ECMs) exert diverse effects on osteogenic differentiation of PDLSCs and accurately control alveolar bone defect repair. Methods : The characteristics of PDLSCs and bone marrow mesenchymal stem cells (BMSCs) with respect to surface markers and multi-differentiation ability were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…Both HOTAIRM1 and HOXA2 inhibited the cell proliferation and promoted calcification formation of hDFSCs. As cells differentiate, their rate of proliferation usually decreases (Wen et al, 2019), suggesting that HOTAIRM1 and HOXA2 may be involved in stem cell fate determination in hDFSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Both HOTAIRM1 and HOXA2 inhibited the cell proliferation and promoted calcification formation of hDFSCs. As cells differentiate, their rate of proliferation usually decreases (Wen et al, 2019), suggesting that HOTAIRM1 and HOXA2 may be involved in stem cell fate determination in hDFSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple differentiation capacities of PDLSCs were determined according to the methods previously described [ 22 , 23 ]. Briefly, PDLSCs were cultured into a 6-well plate in a density of 1 × 10 6 cell per well without inducers until 80% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports confirmed through IF staining processes that pre-osteoblast protein molecules such as ALP, COL1 were developed by Stro-1 small population. The Stro-1 co-expression with ALP in cells in the middle of the process of osteogenic differentiation was confirmed by Gronthos et al [84,85]. In this case, it was demonstrated that osteoblastic progenitors after complete transformation lead to the development of TSCs in stro-1 cells in GCTB which helps them to obtain multipotent nature.…”
Section: Role Of Several Important Factors In the Development Of Gianmentioning
confidence: 56%